The effect of ethical values on transformational leadership and ethical climate in organisations - A. S. Engelbrecht; A. S. Van Aswegen; C. C. Theron (South African Journal of Business Management, 2005)
Ethical leaders are ultimately responsible for developing a strong and sustainable ethical climate in organisations. Ethical values and the ability to influence followers to internalise these values have become prerequisites for effective leadership in modern organisations. Although ethics, leadership, and values have received much attention, there has been little coordinated effort to integrate transformational leadership with ethical climate and ethical values. The aim of this study was to develop and validate a theoretical model to explain the structural relationships between these variables in the South African business context. The results revealed that altruism influences transformational leadership positively, and that transformational leadership in turn has a positive effect on ethical climate. Some support was also found for the proposition that integrity moderates the effect of transformational leadership on ethical climate.
Keywords: 650